Physiological assessment of water deficit in soybean using midday leaf water potential and spectral features - Chathurika Wijewardana; Firas A. Alsajri; J. Trenton Irby; L. Jason Krutz; Bobby Golden; W. Brien Henry; Wei Gao; K. Raja Reddy (Journal of Plant Interactions, 2019)
Drought is one of the major abiotic stresses that limit soybean production worldwide. This study was conducted to determine whether soybean cultivars with divergent growth habits respond differently to drought stress at the vegetative growth stage regarding canopy reflectance, physiological, and gas exchange traits under controlled conditions. Soil moisture content was positively correlated with mid-day leaf water potential. Pooled over cultivar, photosynthesis and stomatal conductance were highly correlated with mid-day leaf water potential, while Ci/Ca exhibited a weak positive correlation. These data indicate that, regardless of cultivar, the decrease in net photosynthesis is mainly due to stomatal closure. For both cultivars, drought stress increased soybean canopy reflectance in the visible range of the spectrum but decreased reflectance in the near-infrared region. The quantified physiological traits would be useful to understand plant water relations and canopy structure to help soybean growers to make field management decisions during the growing season.